2016
DOI: 10.1016/j.bbagrm.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus NS1 protein binds cellular DNA to block transcription of antiviral genes

Abstract: Influenza NS1 protein is an important virulence factor that is capable of binding double-stranded (ds) RNA and inhibiting dsRNA-mediated host innate immune responses. Here we show that NS1 can also bind cellular dsDNA. This interaction prevents loading of transcriptional machinery to the DNA, thereby attenuating IAV-mediated expression of antiviral genes. Thus, we identified a previously undescribed strategy, by which RNA virus inhibits cellular transcription to escape antiviral response and secure its replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 55 publications
0
38
1
Order By: Relevance
“…In particular, we used WSN strains with mutations in the RNA‐binding domain (RBD, R38A/K41A), the effector domain (ED, F103S/M106I and A149V) or the C‐terminal region (Δ221–230) of NS1 . It was shown that these mutations prevent NS1 interactions with dsRNA/DNA, CPSF4, nuclear export machinery or some other cellular and viral factors, and thus suppress the production of IFNs and ISGs . Figure B demonstrates that mutant viruses similar to wild‐type strain reduced the viability of macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we used WSN strains with mutations in the RNA‐binding domain (RBD, R38A/K41A), the effector domain (ED, F103S/M106I and A149V) or the C‐terminal region (Δ221–230) of NS1 . It was shown that these mutations prevent NS1 interactions with dsRNA/DNA, CPSF4, nuclear export machinery or some other cellular and viral factors, and thus suppress the production of IFNs and ISGs . Figure B demonstrates that mutant viruses similar to wild‐type strain reduced the viability of macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain why attenuation of the IFN antagonistic ability of NS1-K108R is independent of RIG-I CARD, TBK-1, and IRF3 activation. In addition, Anastasina et al [41] reported that the NS1 protein binds to cellular DNA to block the cellular transcription of IFNs and ISGs; thus, NS1 proteins retained in the cytoplasm lose their cellular DNA binding function, resulting in impaired IFN-β antagonistic ability.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds (ABT-737, ABT-263, ABT-199, WEHI-539, A-1331852, A-1155463) have different affinities for Bcl-2 proteins [40], but all can universally induce premature death of IAVinfected cells at concentrations not toxic for non-infected cells [44] (Bulanova et al, unpublished). However, only ABT-263, A-1331852 and A-1155463 could effectively limit viral replication and spread.…”
Section: Bcl-2 Inhibitors As Antiviral Compoundsmentioning
confidence: 99%
“…Other cellular proteins including UACA, PAWR, FLII, Trim21, IMMT, 14-3-3, EFHD2, DHX9, DDX3, NLRP3 and LRRFIP2 as well as viral factors M2, PB1-F2, NS1, HA and NP may play important roles in Bcl-2-dependent apoptosis by stabilizing or altering the interactions of BH3-domain proteins in infected cells [44,[46][47][48]. However, further studies are required to verify their specific functions in apoptosis.…”
Section: Apoptosis In Iav-infected Cellsmentioning
confidence: 99%
See 1 more Smart Citation